Production of kombucha from Muntingia calabura L. leaves and evaluation of its antibacterial activity and total flavonoid content - Herwin, Fitriana, Siska Nuryanti (Journal of Applied Pharmaceutical Science, 2022)
Kombucha is a supplement beverage from the fermentation of tea leaves by a symbiotic culture of acidic bacteria and yeast. In this study, we aim to produce kombucha from Muntingia calabura L. leaves and evaluate its characteristics, antibacterial effect, and total flavonoid content. The characteristics of kombucha were evaluated by the established method for the kombucha product. The antibacterial activity was determined by agar diffusion, and the total flavonoid content was assessed by UV-Vis spectrophotometry. Kombucha from M. calabura leaves was produced with acceptable characteristics. The pH and acidity of kombucha were 4.78 and 0.22%, respectively. The alcohol content of kombucha was 0.726%. The value of total plate count (TPC) bacteria and fungi were zero colony forming unit (CFU)/ml and 2 × 100 CFU/ml, respectively. The value of the most probable number of coliform and pathogenic bacteria exhibited the absence of bacterial growth on lactose broth medium and eosin methylene blue agar medium. Kombucha from M. calabura leaves showed a remarkable potency of antimicrobial activity against a pathogenic bacterium, demonstrating the inhibition of the growth of Escherichia coli, Shigella dysenteriae, Salmonella typhi, Bacillus subtilis, and Vibrio cholerae. The total flavonoid content of kombucha was 35 mg/ml quercetin equivalent. The kombucha from M. calabura leaves was produced with good characteristics and safety for a daily beverage. Moreover, it has an antibacterial activity toward some pathogenic bacteria and can be a source of natural flavonoids.
Keywords: Muntingia calabura L., kombucha, fermentation, healthy beverage, flavonoid, antimicrobial